2019
DOI: 10.1200/jgo.18.00245
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Phase II Trial to Compare the Efficacy of Haloperidol and Olanzapine in the Control of Chemotherapy-Induced Nausea and Vomiting in Nepal

Abstract: PURPOSE The purpose of the study was to compare efficacy and toxicity of olanzapine (OLN; a higher-cost drug) and haloperidol (HAL; a lower-cost drug) in the prevention of chemotherapy-induced nausea and vomiting (CINV) in patients who receive highly emetogenic chemotherapy (HEC). PATIENTS AND METHODS In a randomized, phase II trial, patients were randomly assigned to receive either OLN 10 mg orally on days 1 to 4 or HAL 1 mg orally on day 1 and 0.5 mg twice daily on days 2 to 4. Both groups received ondansetr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…6 Both typical and atypical antipsychotics are classes of drugs frequently used for CINV. 8,16,17 The American Society of Clinical Oncology included olanzapine in their 2017 treatment guidelines as a prophylactic agent in highly emetogenic chemotherapy. 16 In a 2019 phase II clinical trial, olanzapine was found to have efficacy similar to haloperidol in the treatment of CINV.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…6 Both typical and atypical antipsychotics are classes of drugs frequently used for CINV. 8,16,17 The American Society of Clinical Oncology included olanzapine in their 2017 treatment guidelines as a prophylactic agent in highly emetogenic chemotherapy. 16 In a 2019 phase II clinical trial, olanzapine was found to have efficacy similar to haloperidol in the treatment of CINV.…”
Section: Discussionmentioning
confidence: 99%
“…16 In a 2019 phase II clinical trial, olanzapine was found to have efficacy similar to haloperidol in the treatment of CINV. 17 However, while haloperidol is more commonly utilized as an antiemetic, the only other case series reporting on the use of olanzapine in CHS found that haloperidol was less effective than olanzapine. 11 Olanzapine is a histaminergic, dopaminergic, serotonergic, and muscarinic antagonist which may explain its antiemetic properties.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have investigated the use of olanzapine as an antiemetic drug (AED) in adult patients undergoing chemotherapy. The findings revealed an effective antiemetic effect compared with aprepitant or metoclopramide and other combinations of AEDs [9][10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 93%
“…Among the adult prophylactic studies, 15 reported exclusively on HEC patients [46, 49-52, 55, 56, 58, 60-66], three exclusively on MEC patients [53,57,59], and three on a patient population that consists of both HEC and MEC patients [45,47,54]. Eight studies compared olanzapine to a double-blind placebo-controlled regimen [47,52,59,[62][63][64][65][66] and thirteen used an opened controlled study design-nine studies used a control arm with antiemetics different from the antiemetics in the investigational (olanzapine-containing) arm [46,49,51,53,55,56,58,60,61] and four used a control arm with the same antiemetics as in the investigational (olanzapinecontaining) arm except for olanzapine [45,50,54,57]. 17 adult prophylactic studies used 10 mg doses of olanzapine [45, 46, 49-59, 61, 62, 65, 66], and 3 studies used 5 mg [47,60,63]; 1 used a mix of 5 mg and 10 mg [64] (Table 1).…”
Section: Included Studiesmentioning
confidence: 99%